Editorial [ Hot Topic:RIPpers at the Membrane - A Brief History of APP Secretases, their Substrates and their Functions (Guest Editors: Dieter Hartmann)] - Hartmann, Dieter (Current Alzheimer Research, 2012)
During the past 12 years, generation of intracellular signals by regulated cleavage of membrane proteins has made its way from a newcomer on the scientific stage (introduced by a battery of key papers appearing between 1998 and 2000, as reviewed in [1]), to a central signaling mechanism, termed Regulated Intramembrane Proteolysis (RIP), now presented in all standard textbooks of cell biology. In retrospect, it is intriguing to see how during the roughly 10 years preceding this breakthrough quite diverse lines of research have laid down the foundation for both the concept itself as well as for the identification of the three APP secretases, which are now accepted as an important machinery for the RIPping of a growing list of functionally important proteins. This story is the more fascinating, as en route with the new signaling paradigm two likewise novel enzyme architectures, disintegrin proteases and i-CliPs, had to enter the scientific stage as well. To start from the perspective of Alzheimers Disease, isolation of Aβ [2] and later APP provided the first example for the constitutive release of protein fragments from the membrane including the then almost unbelievable observation of proteolysis within the membrane plane [3, 4, reviewed in 5]. Further conceptual advances were made possible by the understanding of the SREBP signaling pathway, not only because it was the first one for which the two - step proteolysis scheme was elucidated as a signaling event, but also because it opened the road for the identification of enzymes similar to S2P and thus to RIP in eubacteria, documenting the phylogenetic age and conservation of such signaling techniques (reviewed in [1]). Then - almost ironically - two of the severe familial forms of AD offered a crucial genetic approach to identify and analyze PSEN1 and later PSEN2 and thus the active core of γ-secretase. Specifically, knockout data demonstrated the essential role of PSENs in APP (and later Notch) γ-secretase cleavage, while inhibitor data pointed towards their intramembrane aspartyl protease activity. In parallel, mutagenesis approaches targeting two conserved aspartates at the same transmembrane level in neighbouring TMDs of PSENs confirmed that this unusual proteolytic center is indeed crucial for γ secretase activity. Together, these approaches opened the way to our current understanding of this entirely novel type of an intramembrane - acting enzyme [6, 7], subsequently augmented by the demonstration that PSENs can only act as members of multiprotein complexes, whereby the composition of which would allow for the formation of different isocomplexes with - to some degree - different functional properties [8]....